Polemic Happy Christmas and New Year in Makassar and Alternative Offer - Yusuf, Muhammad; Barsihannoor, Barsihannoor; Rosmini, Rosmini (Universitas Ahmad Dahlan, 2025)
This research reviews the polemic of Muslims in Makassar regarding Christmas and New Year greetings. Furthermore, some proposed various alternative solutions. This research studies the living Quran, namely, how Islamic leaders understand the verses related to the theme. Data collection methods are documentation, focus group discussions, interviews, and observations. Data were analyzed with a qualitative approach. The analysis shows three main points. First, Muslim leaders in Makassar are categorized as having pros and cons in their views on Christmas and New Year greetings. Second, there is the thought of utilizing historical treasures called taqiyya as an alternative to multiculturalism. Shiites and Sunnis agree that there is taqiyya, but they differ in its application. It is at this level that sustainable and ethical dialogue is needed. Third, being united in terms of what is agreed upon and tolerant of differences are the rules for assembling unity and harmony in diversity. Therefore, continuous dialogue must be carried out with the obligation to uphold shared ethics.